Analysis of the calcium-modulated proteins, S100 and calmodulin, and their target proteins during C6 glioma cell differentiation (The Rockefeller University Press, 1989)
We have analyzed the levels, subcellular distribution, and target proteins of two calcium-modulated proteins, S100 and calmodulin, in differentiated and undifferentiated rat C6 glioma cells. Undifferentiated and differentiated C6 cells express primarily the S100 beta polypeptide, and the S100 beta levels are four-fold higher in differentiated compared to undifferentiated cells. Double fluorescent labeling studies of undifferentiated cells demonstrated that S100 beta staining localized to a small region of the perinuclear cytoplasm and colocalized with the microtubule organizing center and Golgi apparatus. Analysis of differentiated C6 cells demonstrated that S100 beta distribution and S100 beta-binding protein profile changed significantly upon differentiation. In addition, the brain-specific isozyme of one S100-binding protein, fructose-1,6-bisphosphate aldolase C, can be detected in differentiated but not undifferentiated C6 cells. While changes in the subcellular distribution of calmodulin were not observed during differentiation, calmodulin levels and calmodulin- binding protein profiles did change. Altogether these data suggest that S100 beta and calmodulin regulate different processes in glial cells and that the regulation of the expression, subcellular distribution, and target proteins of S100 beta and calmodulin during differentiation is a complex process which involves multiple mechanisms.